PEMERTAHANAN BAHASA BALI SEBAGAI BAGIAN PELESETARIAN KEARIFAN LOKAL (Widyadari : Jurnal Pendidikan, 2021)
Balinese language as one of the languages ​​and recorders of Balinese culture is very important to be preserved. The preservation of the Balinese language is also expected to maintain Balinese taksu. The method used in this research is descriptive method. The use of descriptive methods is in accordance with the research objectives, namely describing the efforts that can be made in maintaining the Balinese language as one of the local wisdom. Descriptive method is a fact finding with proper interpretation with the aim of describing or describing systematically, factually, and accurately about the facts, characteristics, and relationships between the phenomena being investigated. The results of the research on Balinese as a vehicle for Balinese culture seem to continue to experience changes on the one hand and conservation efforts on the other. Based on the description of the Balinese language, it occurs at the level of vocabulary used by its speakers towards a humanist language, without anyone feeling higher and being humiliated. The use of words that lead to equality has begun to become clear in its use, especially at the level of alus sor, considering that the word alus sor has been used by all groups of Balinese people in their daily conversations. Meanwhile, the aspect of preserving the Balinese language is closely related to the history of the ancestors of the Balinese people. Balinese speakers are able to respect others in speaking so the introduction of fine language must start early. In its role as the guardian of local wisdom (local genius), apart from maintaining a "Anggah-Ungguh" language attitude, it is also important to innovate by adopting language elements that exist outside of Balinese itself. The custom of the Balinese language is carried out by expanding the media, such as print and writing.